Efficacy of Sphincter Control Training and medical device in the treatment of premature ejaculation: A multicenter randomized controlled clinical trial. - Jesús E Rodríguez; Jose A Picazo; Juan C Marzo; José A Piqueras; Leandro Reina; Guillermo Hidalgo; Guillermo Tornero (PLoS ONE)
A new line of treatment for premature ejaculation (PE) based on the use of masturbation aid device in combination with behavioral techniques has emerged in recent years. We report a multicenter randomized clinical trial with a parallel group design to determine the effectiveness of an electronic device called Myhixel I© in the treatment of PE. Forty patients who met the criteria for the diagnosis of lifelong PE, were assigned to two treatment groups completed the Sphincter control training (SCT) program in eight weeks. The only difference between groups was the use of the device. The main measure was the "fold increase" (FI) of the intravaginal ejaculatory latency time (IELT). The geometric means of IELT show, at the end of the treatment at week 8, a superiority of the device group. The mean FI 4.27 (SD 2.59) at the end of treatment for the device group was clearly higher than obtained in the previous clinical trial, in which a specific medical device was not used. No side effects were observed and it required little therapeutic input and no partner involvement. The SCT program in combination with the Myhixel I© is an effective treatment for PE.